(3Gdbhd GdeLed aj GdQO Ydi Gdegeds - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3jbhd YHO GdQMef Hf CHj HcQ GdSjhWj GdTGaYj GdMeO ddg GdPj GeJMf GdYdeGA hHYO abO bQC HYV GdCbhGe aj BNQ cJGH GdTaG ddbGVj YjGV bhdg hjNUfG HNUjU ReQI fHjfG hLeGYJg abQCgG HSchf GdjGAs
(3BNQgG (B:s
(3aEfg aGQSj eYQH dG YQHj Hd hSLjf CjVG ZjQ YQHj ceG UQM Hg CHh MGJe GddZhj aj cJGH GdRjfIs
(3efbhdI ef fSNI GdeDda GdeDQNI SfI (B886(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 301s
(3eYLe GdeDdajf(B: 2 / 82s
(3cTa GdXfhf(B: 2 / 1364s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs